Biomechanics of soccer equipment - Luhtanen, P. (coachesinfo.com)
About the biomechanicsof the equipment used in soccer, which has a major effect on the way the game is played. The ball itself is of a certain size, construction, weight and pressure, all of which affect the way it responds in play. The ground on which the game is played also affects the nature of the game. Surfaces for soccer have evolved in response to both performance and economic needs. The boot is an important piece of players' equipment and well fitting boots can not only aid comfort but also provide a positive interaction between player and surface to create traction for stopping, starting and turning. Boots aid player-ball interaction for passing and shooting and they must also protect the player and be resistant to the stresses of the game. Shin guards are essential in the modern soccer for protecting against kicks and blows and are mandatory in organized play, but have until recently been neglected in biomechanical investigations.